THE IMPACT OF COVID-19 ON TEACHING AND LEARNING AT UNIVERSITIES - Hung, Pham Duc; Ngan, Duong Thi Thu; Mi, Nguyen Thi Tra; Diem, Nguyen Le Khoa; Tuan, Nguyen Anh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The paper focuses on the analysis of the reports conducted by international organizations in association with the workable solutions implemented at higher education institutions. As a consequence, the paper will draw reasonable conclusions and propose practical measures in teaching and learning activities at the Institute of Industrial Management Logistics IMALOG, Binh Duong University